Characterizing clinical features and location‐specific gene expression profiles associated with pain burden in children with functional dyspepsia. Issue 9 (13th June 2021) - Mokha, Jasmeet S.; Hyams, Jeffrey S.; Glidden, Nicole C.; Balarezo, Fabiola; Young, Erin
Abstract: Background: In children with functional dyspepsia (FD), genes involved in pain modulation may be differentially expressed contributing to chronic pain. Methods: Children with suspected FD (cases) and known eosinophilic esophagitis (controls) undergoing esophagogastroduodenoscopy completed the Rome IV Diagnostic, Pain Burden and Frequency Severity‐Duration questionnaires. Two antral and two duodenal biopsies were collected and relative fold differences in gene expression for 84 pain‐associated genes compared to pain‐free controls were calculated. Results: Sixty‐six subjects with FD (postprandial distress syndrome = 34, epigastric pain syndrome = 7, both = 25; 65% female; mean age 13.7 years) and 13 pain‐free controls (8% female; mean age 12.7) were studied. There were no significant differences in antral and duodenal eosinophilic counts or distribution between the pain and pain‐free groups. Pain severity and burden did not differ significantly between FD subgroups and neither measure significantly correlated with eosinophil counts in the antrum or duodenum. Analysis of 47 antral and 39 duodenal biospecimens revealed 5 candidate genes significantly associated with pain burden: antral EDN1, PTGES3 and duodenal HTR1A, P2Y1, SCN3A ( p  < 0.01). Subsequent stringent statistical analysis comparing those with significant pain versus no pain revealed antral PTGES3 and duodenal SCN3A were the highest priority candidate genes ( p  < 0.001). Conclusions: Pain burden in pediatric FD may be linked to antral EDN1, PTGES3 and duodenal HTR1A, P2Y1, SCN3A differential expression. These genes are known to be involved in pain conduction, modulation, and neurotransmission, suggesting potential therapeutic targets for managing pain in FD. Abstract : Mean fold differences in candidate gene mRNA expression in antrum ( EDN1, PTGES3 ) and duodenum ( HTR1A, P2Y1, SCN3A ) biopsies from patients (collapsed across PDS, EPS, PDS+EPS, and EoE) with pain versus those reporting no pain at the time of diagnosis. Cq values of each gene of interest were normalized to the average Cq values of 3 housekeeping genes ( GAPDH, ACTB, and B2M ) resulting in a Δ Cq for each sample. ΔΔ Cq calculated by normalizing Δ Cq from each sample to the average Δ Cq for healthy control subjects with EoE as the only pain‐free clinical diagnosis. Fold differences in expression are presented as mean ± SEM. Significant differences between groups analyzed with independent samples t test ( p  < 0.01). * =  p  < 0.001.